Tacrolimus Dose Modification in Hematopoietic Cell Transplant Recipients Following a Change in Therapy from Fluconazole to Voriconazole. (24th October 2012) - Guarascio, Anthony J.; Slain, Douglas; Cumpston, Aaron
Abstract : Antifungal therapy with voriconazole or fluconazole in combination with the calcineurin inhibitor tacrolimus exhibits significant CYP3A4 drug interaction potential in allogeneic hematopoietic cell transplant (HCT) recipients. The package insert for voriconazole has dosing recommendations for tacrolimus when voriconazole is started, but these do not apply to patients already receiving fluconazole therapy. The purpose of this retrospective study is to estimate appropriate dose modification of tacrolimus following a change in therapy from fluconazole to voriconazole. We performed a retrospective case-series analysis of five patients. The mean steady-state concentration/dose ( C / D ) ratio of tacrolimus increased from 413 (range, 255–642) to 850 (range, 670–953) following a switch from fluconazole to voriconazole (P = 0.006 ). This data represents a mean 2-fold increase in C / D ratios following the switch, indicating that the dose of tacrolimus may be most accurately reduced by approximately 50% following this switch in therapy. This provides some guidance for practitioners to estimate dose adjustments but will require close pharmacokinetic monitoring and adjustments on an individual patient basis.